Disinfection of indoor air for the inactivation of SARS-CoV-2: a review of the effectiveness of UV-C technology and gaps in research - Rada, Elena Cristina; Vignali, Chiara; Bellazzi, Stefano; Carnevale Miino, Marco; Abbà, Alessandro; Szabó, Márta; Torretta, Vincenzo; Collivignarelli, Maria Cristina (Frontiers in Built Environment, 2025)
Coronavirus disease (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In indoor environments, a structured strategy is needed to reduce the risk of infection. In addition to maintaining proper ventilation and wearing face masks, the development of effective technologies for limiting the transmission of SARS-CoV-2 through infectious respiratory particles (IRPs) has been studied. UV-C devices have already proved effective against other types of microorganisms and have also been investigated for their potential in inactivating SARS-CoV-2. This work aims to review and discuss these findings while also presenting recommendations for future research. Based on the available data, UV-C proved to be effective in the inactivation of airborne SARS-CoV-2 or its surrogates. The main gaps in this research have also been highlighted, and some outlooks for future studies have been suggested. In some studies, the use of surrogates with higher susceptibility to UV-C than airborne SARS-CoV-2 or the consideration of total bacterial counts alone may have led to misleading results. The question “how much variables affect the inactivation rate of airborne SARS-CoV-2 by UV-C in indoor environments?” is still unsolved, considering that the number of studies on the inactivation of this virus in real indoor environments is quite limited. The outcomes of this study can be useful for the scientific community, the technical stakeholders (e.g., managers in the healthcare and transport sectors), and the common people, providing important information about the performance of these technologies to improve the quality of air in indoor environments.